PENGARUH LEVERAGE TERHADAP MANAJEMEN LABA DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - Naftalia, Veliandina Chivan; Marsono, Marsono (Diponegoro Journal of Accounting, 2013)
This research aimed to analyze the influence of leverage to earnings management andÂ the ability to analyze the influence corporate governanceÂ consisting of institusional ownership, managerial ownership, audit quality, and independent commisioner in influencing earnings managemenÂ on the listed manufacturing companies spesifically consumer goods in Indonesia Stock Exchange during years 2009-2011.In this research, there were one dependent variables, one independent variables, and four moderating variables. The dependent variable in this study is earnings management. The independent variable of this study is leverage. Measurement of earnings management using the Modified Jones (1995) as the best estimate of the ability estimate earnings management activities with minimum standard error and standard deviation. Independent variable in this study is leverage. Moderating variable in this study consists of institutional ownership, managerial ownership, quality audits, and independent board.The results showed that leverage significantly influence to earnings management . moderating variables that influence the relationship of leverage to earnings management is institutional ownership. Meanwhile managerial ownership, the proportion of independent board and audit quality is not moderating variables.